Long-term follow-up of a case of amyloidosis-associated chorioretinopathy - Koichi Nagura; Tatsuya Inoue; Jared Ching; Akinori Sato; Shohei Kitahata; Maiko Maruyama-Inoue; Masaru Takeuchi; Kazuaki Kadonosono (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To describe the findings of long-term follow-up of a case of amyloidosis-associated chorioretinopathy by multimodal imagings, including optical coherence tomography (OCT). Observations: A 47-year-old woman who had been diagnosed as having systemic amyloidosis was found to have a best corrected visual acuity of 20/13 in both eyes at the age of 41, which subsequently decreased to 20/100 in the left eye and 20/20 in the right eye at age 47. Visual field examination demonstrated worsening of the central scotoma during the follow-up period. Funduscopic examination revealed bilateral white deposits along the choroidal vessels, which became more pronounced over time, along with diffuse pigmentary changes. The fluorescein angiography and indocyanine green angiography findings were consistent not only with atrophic lesions, but also with amyloid deposition (i.e., staining of the vessels).At the baseline, macula OCT revealed a thick hyporeflective band at the choriocapillaris, however, at the last follow-up, it revealed an absent ellipsoid zone, and bilateral progressive retinal pigment epithelium irregularities in both eyes. Conclusions: Patients diagnosed as having amyloidosis-related chorioretinopathy may have maintained visual function at the first detection of retinal amyloid deposition, and a number of years may elapse before the patient manifests visual deterioration.